Synthesis and biological activity of 3,4-dimethylphenyloxamoyl aminoacids and their salts with D(+)-glucosamine - Alrahawi, K.M.; Petyunin, G.P.; Maloshtan, L.N. (Журнал органічної та фармацевтичної хімії, 2008)
New 3,4-dimethylphenyloxamoylaminoacids and their salts with D-(+)- glucosamine were synthesized. Convenient method of synthesis of optically active oxamoylaminoacids were discovered. The biological screening showed that some compounds have significant hepatoprotective, antiinflammatory and immunodepressant activities with low toxicity. Синтезовані 3,4-диметилоксамоїламінокислоти та їх солі з D-(+)глюкозаміном. Знайдений зручний спосіб синтезу оптично активних оксамоїламінокислот. Біологічний скринінг показав наявність у них гепатопротекторної, протизапальної та імунодепресивної активності при низькій токсичності. Синтезированы 3,4-диметилоксамоиламинокислоты и их соли с D(+)глюкозамином. Найден удобный метод синтеза оптически активных оксамоиламинокислот. Биологический скрининг показал наличие у них гепатопротекторной, противовоспалительной и иммунодепрессантной активности при низкой токсичности.